Squiggles & spaces. Revisiting the Work of D. W. Winnicott - Vilete, Edna (Natureza Humana - Revista Internacional de Filosofia e Psicanálise, 2003)
Resenha de Mario Bertolini et. al., 2001: Squiggles & spaces. Revisiting the Work of D. W. Winnicott. v. 1 e 2. London: Whurr. Publishers. ISBN: 1 86156 271 3 (v. 1). ISBN: 1 86156 278 0 (v. 2)